Answer:
(x-8)(x-5)
Step-by-step explanation:
The only way to solve this equation is to factor it. You would have to use the sum and product rule.
Step-by-step explanation:
You have to substitute... 0, 5, & 10, & 3
y = 2x + 3
y = 2(0) + 3
y = 0 + 3
y = 3
(0,3)
y = 2x + 3
y = 2(5) + 3
y = 10 + 3
y = 13
(5,13)
y = 2x + 3
y = 2(10) + 3
y = 20 + 3
y = 23
(10,23)
y = 2x + 3
y = 2(3) + 3
y = 6 + 3
y = 9
(3,9)
Answer: -15x^3y^7
Step-by-step explanation:
-5x^2y^4(3xy^3)
Multiplty the coefficients
Multiply the x terms
and fianally multiply the y terms
-5(3) = -15
x^2 * x = x^3
y^4* y^3 = y^7
= -15x^3y^7
The first one as the first number must be >= 1 Here it is 0.2.
C would be correct
Hope Your Thanksgiving Goes Well, Here's A Turkey
-TheKoolKid1O1